Comprehensive Analysis of the Relationships Between Tumor Mutation Burden With Immune Infiltrates in Cervical Cell Carcinoma - Zhou, Cankun; Li, Chaomei; Peng, Shunqing; Zhou, Liangcheng; Li, Huan (Frontiers in Molecular Biosciences, 2020)
We aimed to investigate the prognosis of tumor mutation burden (TMB) in cervical cell carcinoma (CCC) and its potential association with tumor-infiltrating immune cells. The data from TCGA were analyzed, and higher TMB levels conferred high overall survival time, associated with higher T staging (p = 0.006) and older age (p =2.961e-04). Through "CIBERSORT" package and Wilcoxon rank-sum test, the high TMB group exhibited higher levels of infiltration of T cell CD8 (p =0.008), T cell CD4 memory activation (p =0.006), T cell follicular assistance (p =0.018), and Macrophage M1 (p =0.037). In addition, 478 TMB-associated differentially expressed genes were identified, and two hub TMB-associated immune genes were identified, including CLEC3B and COL4A2. The TMB prognostic model (TMBPM) based on 2 hub immune genes showed robust prognostic capability in both training set and testing sets, and the higher the TMBPM score, the worse the prognosis. Finally, survival time was higher for high CLEC3B expression levels (p=0.038) and lower for high COL4A2 expression levels (p=0.033). Notably, there is an association between the expression of these two genes and immune infiltration in CCC. CLEC3B expression was most significantly positively correlated with B cells, CD4+ T cells, and Macrophage infiltration. COL4A2 expression was most significantly positively correlated with the presence of Macrophage and Dendritic cell infiltration. In addition, we observed that CLEC3B and COL4A carry mutations in multiple forms that normally suppress immune infiltration, including B cells, CD8+ T cells, and Macrophages.